User modeling, adaptation, and personalization 19th international conference, UMAP 2011, Girona, Spain, July 11-15, 2011 : proceedings - User Modeling, Adaption and Personalization 2011 Girona, Spain) 2011; Konstan, Joseph A.; Conejo, Ricardo; Marzo, José L.; Oliver, Nuria; SpringerLink (Online service). (Berlin SpringerLink, 2011)
This book constitutes the proceedings of the third annual conference on User Modeling, Adaptation and Personalization, UMAP 2011, held in Girona, Spain, in July 2011. This conference emanated from the merger of the successful biannual User Modeling (UM) and Adaptive Hypermedia (AH) conference series in 2009. The 27 long papers and 6 short papers presented together with 15 doctoral consortium papers, and 3 industry panel papers were carefully reviewed and selected from 164 submissions. The tutorials and workshops were organized in topical sections on designing adaptive social applications, semantic adaptive social Web, and designing and evaluating new generation user modeling.
Electronic reproduction.
Keywords: User interfaces (Computer systems) -- Congresses; Human-computer interaction -- Congresses; Electronic books